Using Multilayered Substrate Integrated Waveguide to Design Microwave Gain Equalizer - Yongfei Wang; Dongfang Zhou; Yi Zhang; Chaowen Chang (Advances in Materials Science and Engineering)
This paper presents the design and experiment of a novel microwave gain equalizer based on the substrate integrated waveguide (SIW) technique. The proposed equalizer is formed by an SIW loaded by SIW resonators, which has very compact structure and can compensate for gain slope of microwave systems. Equivalent circuit analysis is given about the proposed structure for a better insight into the structure’s response. A Ku-Band equalizer with four SIW resonators is simulated and fabricated with a multilayer printed circuit board process. The measured results show good performance and agreement with the simulated results; an attenuation slope of −4.5 dB over 12.5–13.5 GHz is reached with a size reduction of 76%.